Projeto e construção de hidrociclones com análise de incertezas e manufatura aditiva - Garcia, Vitor Alves (2022)
Hydrocyclones are industrial equipment used to separate a discrete phase, solid or liquid, from a continuous liquid phase. The performance of these equipment can be assessed considering three criteria, which are separation, concentration capacity and energy consumption, and these aspects are highly dependent on the equipment geometry and dimensions. Moreover, the simultaneous improvement of hydrocyclone performance in these three features constitutes a multi-objective optimization problem since these characteristics are conflicting with each other. Furthermore, in the classical approach of optimization problems, disturbances and uncertainties, which the system is subjected, are not considered. This fact can lead to results that, when applied in practice, do not correspond to the expectations, making their application unfeasible. Therefore, the present work aimed to design hydrocyclones using reliability-based optimization in the multi-objective context. Thus, optimizations were accomplished considering different reliability levels for four study cases, evaluating the separation potential, the concentration capacity and the energy consumption. Hence, some of the obtained hydrocyclones were chosen to be constructed, along with some equipment reported by Garcia (2018), obtained using robust optimization. In this way, the hydrocyclones were fabricated using the additive manufacturing method and they were experimentally tested. The results showed that a raise in reliability level leads, as expected, to changes in the Pareto curves, which can be in the form of a shortening or a displacement from the original curve, depending on which constraints are being activated. Furthermore, it was found that hydrocyclones obtained with reliability tend, in practice, to respect more the constraints defined in the optimization problem. Finally, it was obtained hydrocyclones with good experimental performance in all considered aspects: separation and clarification potential, concentration capacity and energy consumption.